Comparison between ELISA and PCR for Detection of Epstein - Barr virus in children with acute cervical lymphadenitis - Nazim Khan; Neeraj Narayan Mathur; Sunil Kumar Singh Bhadouriya; Balvinder Singh Arora; Nidhi Chaudhary; Dhriti Khullar (Bengal Journal of Otolaryngology and Head Neck Surgery)
Introduction: Among viruses, Epstein Barr Virus is an important cause of acute cervical lymphadenitis. The clinical features of acute Epstein-Barr virus infection overlap those of a variety of other infectious and non-infectious diseases so reliable laboratory tests are important to not only confirm but aid in the differential diagnosis. The aim of the present study was to investigate and compare the diagnostic utility of EBV DNA detection as an adjunct to serological diagnosis of primary EBV infection.